Why, Whom, and How to Screen for Chronic Thromboembolic Pulmonary Hypertension after Acute Pulmonary Embolism - Boon, Gudula J.A.M.; Huisman, Menno V.; Klok, Frederikus A. (Seminars in Thrombosis and Hemostasis, 2020)
Chronic thromboembolic pulmonary hypertension (CTEPH) is considered a long-term complication of acute pulmonary embolism (PE). Diagnosing CTEPH is challenging, as demonstrated by a considerable diagnostic delay exceeding 1 year, which has a negative impact on the patient's prognosis. Dedicated screening CTEPH strategies in PE survivors could potentially help diagnosing CTEPH earlier, although the optimal strategy is unknown. Recently published updated principles for screening in medicine outline the conditions that must be considered before implementation of a population-based screening program. Following these extensive principles, we discuss the pros and cons of CTEPH screening, touching on the epidemiology of CTEPH, the prognosis of CTEPH in the perspective of emerging treatment possibilities, and potentially useful tests and test combinations for screening. This review provides a modern perspective on CTEPH screening including a novel approach using a simple noninvasive algorithm of sequential diagnostic tests applied to all PE survivors.
Keywords: pulmonary embolism; pulmonary hypertension; diagnostic screening programs; earlier diagnosis; prognosis